Studi Dampak Pengajaran Tim menggunakan Model Rasch Analisis - Faizar Abdurrahman; Muhammad Ihsan; Bakhtiar S (Yayasan Hurriah, Banda Aceh, 2020)
English; This study examines the teaching methods of the team at the Department of Industrial Engineering, Malikussaleh University. Two sets of questionnaires were distributed for lecturers and students to find out their perceptions of team teaching. A total of 12 lecturers and 153 students were selected as respondents. Rasch analysis was used to measure the reliability and validity of the survey instruments used to evaluate the team teaching system. The questionnaire data were then analyzed to identify the reliability of the team teaching method, and to measure its impact on students and lecturers. The results of data analysis indicate that the survey questions were developed with good individual and system reliability. Most of the respondents provide good feedback on team teaching practices. Thus, students and lecturers consider the team teaching method to be effective and have a positive impact on the lecture process. Bahasa; Studi ini menguji metode pengajaran tim di Jurusan Teknik Industri, Universitas Malikussaleh. Dua set kuesioner dibagikan untuk dosen dan mahasiswa untuk mengetahui persepsi mereka tentang pengajaran tim. Sebanyak 12 dosen dan 153 mahasiswa dipilih sebagai responden. analisis Rasch digunakan untuk mengukur kehandalan dan validitas instrumen survei yang digunakan untuk mengevaluasi sistem pengajaran tim. Data quisioner kemudian dianalisis untuk mengidentifikasi kehhandalan metode pengajaran tim, dan untuk mengukur dampaknya terhadap mahasiswa dan dosen. Dari hasil analisa data menunjukkan bahwa pertanyaan survei dikembangkan dengan kehandalan individu dan sistem yang baik. Sebagian besar responden memberikan umpan balik yang baik untuk praktik pengajaran tim. Dengan demikian, mahasiswa dan dosen menganggap metode pengajaran tim efektif dan berdampak positif dalam proses perkuliahan.